PENERAPAN MODEL PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) PADA PEMBELAJARAN IPS SISWA SEKOLAH DASAR: LITERATUR REVIEW - Hasnih, Hasnih; Nasution, Nasution; Jacky, M. (Lembaga Penelitian dan Pendidikan Mandala, 2022)
The purpose of this study is to determine the application of the value clarification technology learning model (VCT) in social studies learning for elementary school students. The research method in this study used documents obtained from previous studies. Sources of library program information are also from a review of previous research that has the same goal. The test in this study was intended to obtain and analyze several VCT learning models in social studies learning for elementary school children. The results of this study include eight articles that were reviewed based on references, research methods, and interventions. The conclusion reached in this study is the Value Clarification Technology (VCT) learning method improves learning outcomes, problem solving skills, aspects of religious values, worship obedience, tolerance, discipline, caring for friends, discussion and having a sense of responsibility to complete tasks correctly. time, imitating the heroism and patriotism of the figures in their environment, and learning motivation in social studies learning for elementary school students.